2006
DOI: 10.1523/jneurosci.5542-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Suppression in Macaque Primary Visual Cortex

Abstract: The response of a neuron in primary visual cortex (V1) to an optimal stimulus in its classical receptive field (CRF) can be reduced by the presence of an orthogonal mask, a phenomenon known as cross-orientation suppression. The presence of a parallel stimulus outside the CRF can have a similar effect, in this case known as surround suppression. We used a novel stimulus to probe the time course of cross-orientation suppression and found that it is very fast, starting even before the response to optimal excitato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
96
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 48 publications
(95 reference statements)
12
96
1
Order By: Relevance
“…To determine the evolution of the extraclassical surround over time, orientation tuning profiles of the surround were plotted at successive time points and SSI, ISD, Iso supp and Ortho supp were calculated for each. Responseonset was defined as the earliest time that the response to the stimulus reached 5% of its maximum with respect to spontaneous activity, similar to previous reports (Smith et al, 2006;Alitto and Usrey, 2008). Importantly, the response onset times of the optimal center alone, iso-surround, and orthosurround conditions did not vary significantly (p = 0.18, analysis of variance (ANOVA); see Fig.…”
Section: Discussionsupporting
confidence: 60%
“…To determine the evolution of the extraclassical surround over time, orientation tuning profiles of the surround were plotted at successive time points and SSI, ISD, Iso supp and Ortho supp were calculated for each. Responseonset was defined as the earliest time that the response to the stimulus reached 5% of its maximum with respect to spontaneous activity, similar to previous reports (Smith et al, 2006;Alitto and Usrey, 2008). Importantly, the response onset times of the optimal center alone, iso-surround, and orthosurround conditions did not vary significantly (p = 0.18, analysis of variance (ANOVA); see Fig.…”
Section: Discussionsupporting
confidence: 60%
“…Although there are close comparisons between our psychophysical experiments on humans and single-cell work in cat (see above), little related work has been done in monkey (though see Smith et al, 2006) and analogous experiments have not been performed. Other work performed by Macknik and his colleagues (Tse et al, 2005;Macknik and Martinez-Conde, 2004) used a very different type of stimulus in which the mask and test contained similar oriented contours, but were not superimposed in either space or time.…”
Section: Implications and Comparison With Other Studiesmentioning
confidence: 73%
“…Thus, if a subgroup of cells in V1 (e.g. in layer 4), were to share the crucial properties of cells in the LGN, we could not rule out the possibility that the broadband ipsiocular effects reside there (see also Smith et al, 2006;Webb et al, 2005).…”
Section: Interocular Suppression Of Binocular Masksmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature selectivity is usually manifest from the first spike of the response (2) and is assumed to be due to hard wiring in the network and to a certain extent a feed-forward process (3). When an animal searches for a visual target among distractors it is not unreasonable to assume that neurons in the brain will be selective for the search target, and we have recently shown that neurons in the lateral intraparietal area of the monkey (LIP) become selective for the target in a visual search task even when the monkey makes a saccade away from the receptive field (4).…”
mentioning
confidence: 99%